RELIGIOUS EVENT (DOOM) AND PURITAN TEACHING IN MICHAEL WIGGLESWORTH’S POEM THE DAY OF DOOM - Riris Yusrina (Rubikon : Journal of Transnational American Studies, 2022)
American literature was strongly influenced by English literature because it was brought by the English colonies who came to America. The Colonial Period in American literature occurred from 1607 until 1775. Many writers had an important role in this period, such as John Winthrop, Anne Bradstreet, William Bradford, and William Wigglesworth. The colonial period started in the colonial era, one hundred years before the Revolution War. The Characteristics of the colonial Period such as historic, simple, religious, and influenced by the English tradition. One of the religious poems written in that era was Michael Wigglesworth’s “The Day of Doom”. It became one of the most famous poems from the Colonial Period. The puritan concept strongly existed in it, especially the Calvinism theology. Calvinist Theology has five concepts. They are Total and innate Depravity, Unconditional Election, Prevenient and irresistible grace, Perseverance of Saints, and Limited Atonement. The poem also represents the Day of Judgement which provides the conversation between God and the man.